Analysis of Development of Biology Teacher Performance Assessment to Assess Students in Practicum Activities - Amnayroh Amnayroh; Novi Indah Suryati (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: This study aims to analyze the development of biology teacher performance assessments to assess students who are in practicum activities at SMA Negeri Batanghari Regency. Methodology: This research is included in the quantitative descriptive research. The subjects in this study were biology teachers in class X and XI IPA at SMA Negeri 1 and 2 Batanghari Regency. The analysis carried out by the researcher included: performance task indicators, performance rubrics, and assessment methods. The research data was obtained from the results of observation sheets, self-assessment questionnaires and peer assessment questionnaires, as well as documentation. Main Findings: Based on research on the analysis of the development of biology teacher performance assessments to assess students in practicum activities at SMA Negeri Batanghari Regency, the overall percentage results obtained were in a good category for SMA Negeri 1 (69.5%) and in a bad category for SMA Negeri 2 (48.4 %). Based on the overall results, it can be concluded that the biology teachers at SMA Negeri 1 and 2 have made performance assessments in practicum activities, but the performance assessments that have been made are incomplete. This is because the biology teacher still has not made clear performance assignments for each practicum activity to be carried out. In addition, the teacher in making rubrics did not include clear scoring. Novelty/Originality of this study: It is expected that Biology teachers need to understand the importance of performance assessment in practicum activities by participating in training or seminars in order to achieve competence and goals in accordance with the educational curriculum.